Specyfika rachunkowości i controllingu w zarządzaniu ryzykiem małych przedsiębiorstw o dużej intensywności procesów gospodarczych - Kluge, Paul-Dieter; Orzeszko, Paweł (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article deals with small enterprises in which ERP solutions serve to fulfil the increased demand for the realization of processes. The paper discusses the aspects of planning and carrying out analysis of plan/accomplishment deviation in particular concerning the results of marketing-mix on prices and costs as well as costs planning and their calculation. The article presents both concepts and test results. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 122-131